The Effectiveness Of Reading Aloud To Improve Students’ Reading Comprehension: Efektivitas Membaca Dengan Keras Untuk Meningkatkan Pemahaman Membaca Siswa - Yuliani, Novi Dwi; Raudah, Siti; Apriliani, Halimah (Nusantara Journal of Education and Social Science, 2024)
At the junior high school level, English is a compulsory subject. Currently, there are many learning methods and media in teaching English, such as media images, slides, videos, etc. However, most teachers still use media in the form of text or reading. There are several techniques that can be used in reading skills, in this study the researcher focused on the 'reading aloud technique' as a teaching method to improve reading comprehension. This research was conducted on class VIII students of MTsN Al-Ikhwan Banjarmasin with a sample of 20 students who were divided into 2 classes, namely control and experimental classes. The test is carried out using multiple choice text. The study took place in 5 meetings with details: 1 pre-test and post-test for the experimental and control classes, 3 treatments using the reading aloud technique in the experimental class. The results of the study were processed using a quantitative approach, the following results were obtained: Average pretest value for the control class: 80, average posttest: 50. Meanwhile in the experimental class, average pretest: 70 and average posttest score: 75 Based on the results this average, it can be stated that the Reading Aloud technique is effective.